Domestic Violence and the Paradox of Post-Separation Mothering - Holt, Stephanie (My University, 2017)
This paper reports selectively on findings from a mixed-methods study to consider the paradoxical post-separation position many women find themselves occupying when child contact necessitates the continued and mainly unmonitored presence of abusive men in their lives and the lives of their children (Holt, 2011). Having engendered blame and being held responsible for the exposure of their children to domestic abuse, mothers may find themselves resisting post-separation child contact and again engendering blame for daring to interfere with the father–child relationship—the same relationship they were charged with protecting their children from. Echoing Thiara and Humphreys’s (2015) call for social worker practitioners to recognise that domestic abuse can continue even in the abuser’s absence, this paper reflects on an issue of particular relevance to social work practitioners—that the continued presence of domestically abusive men, post separation, may compromise the child’s recovery from the experience of domestic abuse due to continuing abuse and undermining of the maternal role and mother–child relationship.
Keywords: Post-separation contact; Mothering through fear; Gendered practice; Child-centred assessment; Inclusive Society; FAMILY; PROFESSION; Emotional-behavioural Problems; Children; Gender; Home and community living; Legislation; Relationships; Social services, interventions and supports